Project Communication Management in a Micro Small Medium Enterprises (MSMES) in a Construction Project - Irvan Wiradinata (Institut Teknologi Nasional, Bandung, 2023)
ABSTRACTMicro, small, and medium enterprises (MSMEs) have become Indonesia's most essential and strategically important national economic drivers. This research focuses on an MSME involved in a construction project in 2021. This research aims to shed light on the project communication management of an MSME organization, PT Nata Kota Nusantara, simply Natakota, a micro-scale enterprise based in Bogor. Natakota was engaged in a civil construction project in a remote site area at PT GDE (GDE) in Ciwidey, Bandung. GDE is a state-owned enterprise focusing on geothermal energy and power generation. Virtual ethnography, observation, and discourse analysis were performed to reveal the project communication management process within the organization. It was unveiled that Natakota used Google Spreadsheet as a form of free and open-source software (FOSS) as their primary communication tool during the project execution. Actor-Network Theory (ANT) explains that the actor is the prime entity that shapes, drives, and accelerates the communication process within the network. This research observed the communication and collaboration between employees on several Google Spreadsheet files. In a project execution phase, communication is essential to obtain a productive project. Project communication plays a central part in communicating information flow to execute that project successfully. The results of this research show that several features in Google Spreadsheet play as actors in the ANT framework, which shapes, drives, and accelerates the internal communication process in the organization. Additionally, it appears that Google Spreadsheet could offer a competitive low-cost option for MSMEs looking to manage internal communications effectively and efficiently.Keywords: collaboration, communication, MSMEs, organization, project